How to research - Blaxter, Loraine , 1945-; Hughes, Christina , 1952-; Tight, Malcolm (Open UP study skills, 2010)
Including chapters on planning and carrying out small-scale research projects, this practical guide takes the reader step-by-step through the research process, from writing proposals to completion of the project. As well as exercises, it also gives advice on writing proposals and making presentations